GERMINATION OF Melocactus bahiensis (CACTACEAE) IN DIFFERENT SUBSTRATES AND TEMPERATURES - LONE, Alessandro Borini; TAKAHASHI, Lúcia Sadayo Assari; FARIA, Ricardo Tadeu de; UNEMOTO, Lílian Keiko (Scientia Agraria, 2007)
The seeds from different species present variable behavior for temperature and substratum in the germination process, and this can provide information of biological and ecological interest. In relation to the tropical species, there is insufficient knowledge about the requirement of the seed when it is related with the different factors involved in the germination. In this way, the objective of this paper was to evaluate the influence of the temperature and substratum in the germination of Melocactus bahiensis seeds. The germinations were analyzed in constant temperatures of 20, 25 and 30 ºC, and alternated temperatures of 20-30 ºC in sand and filter-paper substratum. The variables evaluated were the germination speed index, percentage of germination and the height of the aerial part of seedling. The highest percentage of germination and germination speed index were at 25 ºC and there were not differences between the substrates tested. For the height of the aerial part of seedling, the results showed that there was not variation in function of the temperature for the sand substratum, being the averages higher than the filter-paper substratum. The best conditions for the conduction of germination test of Melocactus bahiensis’s seeds are sand substratum and temperature of 25 ºC.